Synthesis, characterization and biological assessment of a novel hydrazone as potential anticancer agent and enzyme inhibitor - Noma, Samir Abbas Ali; Erzengin, Mahmut; Tunc, Tuncay; Balcioglu, Sevgi (Elsevier, 2020)
In present work, a novel hydrazone compound, namely 1-(5-bromo-2,3-dimethoxybenzylidene)-2-(pyridine-2-yl) hydrazine (5Br2DM2PH), was synthesized by condensation reaction in acidic conditions. The structure of this compound was detailed elucidated by H-1 NMR, FT-IR, UV/VIS and XRD methods. Antioxidant activity of the 5Br2DM2PH compound was investigated by scavenging activity on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals. The 5Br2DM2PH compound exhibited high scavenging activity compared with reference antioxidant. To determine in vitro cytotoxic effect of its, cell viability was tested using MTT assay on human breast (MCF-7) and colon (Caco-2) cancer cell lines. The results showed that the cytotoxic effect of the 5Br2DM2PH is more potent than cisplatin. The IC50 value for MCF-7 is 16.8 mu M while the value for Caco-2 is 11.8 mu M. In addition, the in vitro inhibitory property of the compound 5Br2DM2PH was carried out on human paraoxonase-1 (hPON-1) and the IC50 value was found as 13.8 mu g. Our ambitions for the novel 5Br2DM2PH compound will guide many future studies in the field of medicine, analytical and drug applications, as well as new organic synthesis. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Hydrazone; Anticancer; Antioxidant; Human paraoxonase-1 (hPON-1)